Base-free Pd-MOF catalyzed the Suzuki-Miyaura cross-coupling reaction of arenediazonium tetrafluoroborate salts with arylboronic acids. Issue 40 (4th October 2019) - Liu, Yangyang; Wang, Jie; Li, Tang; Zhao, Zesheng; Pang, Wan
Abstract: A convenient and environmental benign synthesis of biaryls has been demonstrated by a straightforward reaction catalyzed by the palladium-containing metal-organic framework (Pd-MOF) [Pd (2-pymo)2 ]n (2-pymo = 2-pyrimidinolate). A series of functionalized biaryl derivatives have been synthesized in good to excellent yields by the Suzuki-miyaura cross-couplings of sustainable arenediazonium salts with a variety of arylboronic acids and the reactions were catalyzed by the Pd-MOF using methanol as a benign solvent. Those base- and additive-free catalytic reactions proceeded smoothly under non-anhydrous and non-degassed condition. Such transformation avoided high reaction temperature, tolerated many functional groups and presented a wide substrate scope. The catalyst could be recovered by filtration and reused for four successive cycles before collapse of the MOF structure. Graphical abstract: A convenient and environmental benign synthesis of biaryls has been demonstrated by a straightforward reaction catalyzed by the palladium-containing metal-organic framework (Pd-MOF) [Pd(2-pymo)2]n (2-pymo = 2-pyrimidinolate). Fonts or abstract dimensions should not be changed or altered.Image 1 Highlights: A convenient and environmental benign synthesis of a series of functionalized biaryl derivatives has been demonstrated by a straightforward reaction catalyzed by the palladium-containing metal-organic framework (Pd-MOF) using methanol as a benign solvent. The present base- and additive-free catalytic reactions proceeded smoothly under non-anhydrous and non-degassed condition. Such transformation avoided high reaction temperature, tolerated many functional groups and presented a wide substrate scope. The palladium catalyst (Pd-MOF) shows good to excellent yields towards a series of arenediazonium tetrafluoroborated salts and can be simply recovered and reused up to four cycles. This study indicates that the strategy can serve as a general approach for the development of Pd-MOF heterogeneous catalyst for practical catalytic applications.